HSP90 inhibitor (NVP-AUY922) enhances the anti-cancer effect of BCL-2 inhibitor (ABT-737) in small cell lung cancer expressing BCL-2. (28th December 2017) - Yang, Hannah; Lee, Mi-Hee; Park, Intae; Jeon, Hanwool; Choi, Junyoung; Seo, Seyoung; Kim, Sang-We; Koh, Gou Young; Park, Kang-Seo; Lee, Dae Ho
Abstract: Small cell lung cancer (SCLC) cannot be efficiently controlled using existing chemotherapy and radiotherapy approaches, indicating the need for new therapeutic strategies. Although ABT-737, a B-cell lymphoma-2 (BCL-2) inhibitor, exerts anticancer effects against BCL-2-expressing SCLC, monotherapy with ABT-737 is associated with limited clinical activity because of the development of resistance and toxicity. Here, we examined whether combination therapy with ABT-737 and heat shock protein 90 (HSP90) inhibitor NVP-AUY922 exerted synergistic anticancer effects on SCLC. We found that the combination of ABT-737 and NVP-AUY922 synergistically induced the apoptosis of BCL-2-expressing SCLC cells. NVP-AUY922 downregulated the expression of AKT and ERK, which activate MCL-1 to induce resistance against ABT-737. The synergistic effect was also partly due to blocking NF-κB activation, which induces anti-apoptosis protein expressions. However, interestingly, targeting BCL-2 and MCL-1 or BCL2 and NF-κB did not induce the cytotoxicity. In conclusion, our study showed that combination of BCL2 inhibitor with HSP90 inhibitor increased activity in in vitro and in vivo study in only BCL-2 expressing SCLC compared to either single BCL2 inhibitor or HSP inhibitor. The enhanced activity might be led by blocking several apoptotic pathways simultaneously rather than a specific pathway.